2018
DOI: 10.4103/aam.aam_69_17
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of AgNOR counts and pap stain in exfoliative cytology specimens of oral mucosa in bidi smokers and nonsmokers

Abstract: Background: Bidi smoking is a serious health hazard which is common throughout South Asia and parts of the Middle East. It has been strongly implicated to various benign and malignant lesions of oral cavity and oropharynx. These tobacco-filled leaves deliver more than three times the amount of nicotine, carbon monoxide, and tar as cigarettes which exert injurious effects on cells reflected in terms of accelerated proliferative activity in normal oral mucosal cells. Aim: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…AgNORs count method was widely used in oral exfoliative cytology particularly among cigarette smokers to predict early cellular proliferative activity indicating neoplastic change [ 19 ], but its use for lung cytology is scarce [ 20 ]. It was reported that cellular proliferative quantified by AgNORs might play a substantial role in the early detection and diagnosis of premalignant and malignant lesions in the absence of clinical manifestations [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…AgNORs count method was widely used in oral exfoliative cytology particularly among cigarette smokers to predict early cellular proliferative activity indicating neoplastic change [ 19 ], but its use for lung cytology is scarce [ 20 ]. It was reported that cellular proliferative quantified by AgNORs might play a substantial role in the early detection and diagnosis of premalignant and malignant lesions in the absence of clinical manifestations [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further long-term studies which include large sample sizes comparing bidi and cigarette smokers need to be carried out to determine this. 8,9 Autoimmune Disorders Affecting Oral Cavity…”
Section: Application Of Oral CDX Brush Biopsy In Oral Cancer Detectiomentioning
confidence: 99%
“…Further long-term studies which include large sample sizes comparing bidi and cigarette smokers need to be carried out to determine this. The lower plasma lipid status may be a useful bio-marker indicator for initial changes occurring in neoplastic cells .. 21,22 CA 125 is a tumor marker for epithelial ovarian cancer. Elevated salivary levels of CA 125 were detected in patients with epithelial ovarian cancer as compared to patients with benign pelvic masses and healthy controls.…”
Section: Malignancymentioning
confidence: 99%